2008
DOI: 10.1002/cbdv.200890209
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antimalarial Activity of Chemical Constituents from Diospyros quaesita

Abstract: Bioassay-directed fractionation led to the isolation of seven compounds from a sample of the dried leaves, twigs, and branches of Diospyros quaesita Thw. (Ebenaceae). One of the isolates, betulinic acid 3-caffeate (1), showed in vitro antimalarial activity against Plasmodium falciparum clones D(6) (chloroquine-sensitive) and W(2) (chloroquine-resistant) with IC(50) values of 1.40 and 0.98 microM, respectively. Evaluation of compound 1 in the human oral epidermoid (KB) cancer cell line revealed cytotoxicity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Although the plant is not traditionally known in Cameroon to treat malaria, the present study may provide some scientifi c basis on which traditional usage of Diospyros sanza-minika extracts could be encouraged. Several studies have indeed documented the antimalarial potency of crude extracts from the genus Diospyros as well as that of some of their antimalarial constituents (Likhitwitayawuid et al, 1999;Ma et al, 2008;Kantamreddi and Wright, 2008), which were generally found to be triterpenes such as betulinic acid 3-caffeate from Diospyros quaesita (Ma et al, 2008) and naphthoquinones such as diospyrin from Diospyros montana (Likhitwitayawuid et al, 1999). Bergenin, an isocoumarin previously isolated from Diospyros sanza-minika (Musgrave and Skoyles, 1974) was found to be inactive against P. falciparum and only weakly active against P. berghei (Silva et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the plant is not traditionally known in Cameroon to treat malaria, the present study may provide some scientifi c basis on which traditional usage of Diospyros sanza-minika extracts could be encouraged. Several studies have indeed documented the antimalarial potency of crude extracts from the genus Diospyros as well as that of some of their antimalarial constituents (Likhitwitayawuid et al, 1999;Ma et al, 2008;Kantamreddi and Wright, 2008), which were generally found to be triterpenes such as betulinic acid 3-caffeate from Diospyros quaesita (Ma et al, 2008) and naphthoquinones such as diospyrin from Diospyros montana (Likhitwitayawuid et al, 1999). Bergenin, an isocoumarin previously isolated from Diospyros sanza-minika (Musgrave and Skoyles, 1974) was found to be inactive against P. falciparum and only weakly active against P. berghei (Silva et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Malaria is a major threat to global health with ca. 40% of the world's population being exposed to this parasite (Ma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no bio-prospecting and isolation work from the Lao PDR has thus far proceeded to the stage of patent filing thereby meriting additional studies (unlike for Vietnam; Zhang et al, 2014Zhang et al, , 2017, through the VietnamLaos ICBG, six medicinal plant taxa from around the country have been evaluated through the compound isolation stage and have been found to contain mostly novel phytochemicals bearing anti-tuberculosis , anti-malarial (He et al, 2005(He et al, , 2006Libman et al, 2008;Ma et al, 2008); and cancer cell cytotoxicity activities (Zhang et al, 2004). With respect to anticancer bio-prospecting from the ICBG field work conducted from 1998 to 2012 in the Lao PDR, at least 34 species yielded 50 extracts with significant activity (IC 50 < 20 μg/ml) in one or more cancer cell lines of a six cell line panel, which notably led to the isolated compounds asparacoside and 3''-methoxy-nyasol (IC 50 > 4 μg/ml, < 10 μg/ml) from Asparagus cochinchinensis (Lour.)…”
Section: Prior Results and Integrative Programing In Laos Andmentioning
confidence: 99%
“…6 Other studies have also reported the antimalarial potential of that compound and its derivatives. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] A few tetracyclic diterpenes have also shown antimalarial properties. One example is a norpimaran lactone (1d, Figure 1) obtained from manool, 21 and another is kaurenoic acid (3a, Figure 3) described as weakly active.…”
Section: Introductionmentioning
confidence: 99%